Design and Build A Stress Diagnosis System Based on the Internet of Things (Iot) Using the Fuzzy Logic Method - Dharmayanti, Cokorda Istri; Sugianta, I Kadek Arya (Indonesian Journal of Global Health Research, 2024)
Stress is a situation in which an individual feels highly pressured. Numerous studies in the fields of psychology and health predominantly indicate that stress has a negative impact on health. An instrument for measuring stress levels using fuzzy logic methods is a tool used to gauge the level of anxiety or pressure experienced by individuals by observing parameters such as heart rate, body temperature, and blood pressure. Arduino Uno R3 is employed as a data processor, DS18B20 as a sensor for measuring body temperature, and MPX5050DP as a sensor for measuring heart rate and blood pressure. The results of these parameter measurements are then compared with a table that determines stress levels using the fuzzy method as a decision-making guide. Body temperature measurements using the DS18B20 sensor achieves an accuracy rate of 99.48%, while measurements of systolic and diastolic blood pressure and heart rate using the MPX5050DP sensor have accuracies of approximately 91.94%, 89.59%, and 96.7%, respectively. The calculation of stress levels using the fuzzy method operates effectively, with a success rate of 100%, in accordance with manually conducted fuzzy analysis.